Implementasi Teologis Frasa “Mengutus” dalam Yohanes 17:18; 20:21 bagi Gereja dari Perspektif Missio Dei - Manurung, Well Therfine Renward; Kiamani, Andris; Eunike, Meichella Yosepha; Ohoitimur, Reynhard Leonard; Ginting, Samuel Sukanta (Jurnal Salvation, 2024)
Abstract: The church is a fluid fellowship of believers (liquid church). An organism created by Jesus Christ Himself as a tangible manifestation of Christ in the world to do His work: calling sinners and proclaiming the gospel of God as an expression of God's love to the world. This research is motivated by the lack of research that explains the relationship between sending and missio Dei, as well as the limitation of mission to evangelism and church growth, the lack of attention to the importance of dialogue and engagement with society, and the neglect of the complex social and political context in which mission is carried out. This research uses a qualitative method with an interpretative approach (interpretative design) so as to find the meaning and implementation of the phrase "sending" in John 17:18; 20:21: First, the model of sending in John 17:18; 20:21 is parallel, but different in terms of time and to whom the vision is conveyed. this approach is in line with the Theocentric which makes God the starting point of life, His goals, plans, and programs. Second, the church, or fellowship of believers and Great Commission, is the means or instrument of missio Dei. Third, as one form of God's involvement in the world, believers and church members must be actively in preaching the gospel and continuously involved in the Great Commission of the Lord Jesus. The Holy Spirit plays an active role in continuing to assist and participate in this process. Fourth, the role of mission is very important in the initial process of preaching the gospel so engagement and compassion are required. Fifth, formulate a strategy for planning, developing tasks, and understanding His calling as a messenger in delivering the gospel. Abstrak: Gereja adalah suatu persekutuan orang-orang percaya yang selalu bergerak dengan cair (liquid church). Suatu organisme yang diciptakan oleh Yesus Kristus sendiri sebagai perwujudan nyata dari Kristus di dunia untuk melakukan pekerjaan-Nya: memanggil orang-orang yang berdosa dan memberitakan Injil Allah sebagai suatu pernyataan kasih Allah kepada dunia. Penelitian ini dilatar belakangi oleh minimnya penelitian yang menjelaskan keterkaitan antara pengutusan dan missio Dei, serta pembatasan misi hanya kepada penginjilan dan pertumbuhan gereja, kurangnya perhatian terhadap pentingnya dialog dan keterlibatan dengan masyarakat, serta pengabaian terhadap konteks sosial dan politik yang kompleks di mana misi dilakukan. Penelitian ini menggunakan metode kualitatif dengan pendekatan interpretative (interpretative design) sehingga dapat menemukan makna dan implementasi teologis frasa “mengutus” dalam Yohanes 17:18; 20:21: Pertama, model pengutusan dalam Yohanes 17:18 ; 20:21 paralel, tetapi berbeda pada sisi waktu dan kepada siapa visi tersebut disampaikan, pendekatan ini sejalan dengan Teosentris yang menjadikan Allah sebagai titik awal kehidupan, tujuan, rencana, dan program-Nya. Kedua, gereja, atau persekutuan orang-orang percaya dan Amanat Agung, adalah sarana atau alat missio Dei. Ketiga, sebagai salah satu bentuk keterlibatan Allah di dunia, orang-orang percaya dan anggota gereja harus terlibat secara aktif dalam pemberitaan injil dan berkelanjutan dalam Amanat Agung Tuhan Yesus. Keempat, peran pengutusan sangat penting dalam proses awal pemberitaan Injil sehingga diperlukan keterlibatan dan belas kasihan. Kelima, merumuskan strategi perencanaan, pengembangan tugas, dan pemahaman akan panggilan-Nya sebagai utusan dalam menyampaikan kabar Injil.